Editorial: The challenge of peruvian modernity, realities, consequences and university reflections - El Director (2005)
Responding to the will expressed many times by the Academic Community of our Faculty, IECOS has decided to start the publication of its journal with the determination that it will be a prolonged effort in time, that it will not be reduced to this first publication and that it will be improved in form and content.